Role of F-box Protein Cdc4 in Fungal Virulence and Sexual Reproduction of Cryptococcus neoformans - Wu, Ting; Fan, Cheng-Li; Han, Lian-Tao; Guo, Yuan-Bing; Liu, Tong-Bao (Frontiers in Cellular and Infection Microbiology, 2022)
Cryptococcus neoformans is an opportunistic yeast-like pathogen that mainly infects immunocompromised individuals and causes fatal meningitis. Sexual reproduction can promote the exchange of genetic material between different strains of C. neoformans, which is one of the reasons leading to the emergence of highly pathogenic and drug-resistant strains of C. neoformans. Although much research has been done on the regulation mechanism of Cryptococcus sexual reproduction, there are few studies on the sexual reproduction regulation of Cryptococcus by the ubiquitin-proteasome system. This study identified an F-box protein, Cdc4, which contains a putative F-box domain and eight WD40 domains. The expression pattern analysis showed that the CDC4 gene was expressed in various developmental stages of C. neoformans, and the Cdc4 protein was localized in the nucleus of cryptococcal cells. In vitro stress responses assays showed that the CDC4 overexpression strains are sensitive to SDS and MMS but not Congo red, implying that Cdc4 may regulate the cell membrane integrity and repair of DNA damage of C. neoformans. Fungal virulence assay showed that although the cdc4Δ mutant grows normally and can produce typical virulence factors such as capsule and melanin, the cdc4Δ mutant completely loses its pathogenicity in a mouse systemic-infection model. Fungal mating assays showed that Cdc4 is also essential for fungal sexual reproduction in C. neoformans. Although normal mating hyphae were observed during mating, the basidiospores’ production was blocked in bilateral mating between cdc4Δ mutants. Fungal nuclei development assay showed that the nuclei failed to undergo meiosis after fusion inside the basidia during the bilateral mating of cdc4Δ mutants, indicating that Cdc4 is critical to regulating meiosis during cryptococcal mating. In summary, our study revealed that the F-box protein Cdc4 is critical for fungal virulence and sexual reproduction in C. neoformans.